2011
DOI: 10.1007/s10803-011-1410-y
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of Action Intentions in Autism Spectrum Disorder

Abstract: We investigated whether individuals with a mild form of autism spectrum disorder (ASD) are influenced by an actor's gaze direction when anticipating how an observed action will continue in the immediate future. Participants observed a head rotate towards them, while the gaze direction was either leading, or lagging behind, rotation. They also observed identical rotations of a cylinder containing the geometrical equivalent of the gaze manipulation. The control group was influenced by the gaze manipulations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…We consider this as one possible approach toward measuring implicit processes to make them comparable to explicit processes with the new Face Puzzle tasks. With regard to the literature on implicit processing of social information in general (e.g., Hudson et al, 2009; Hudson and Jellema, 2011) and related impairments in ASD (Jellema et al, 2009; Hudson et al, 2012; Senju, 2013), previous studies used mostly tasks that assessed unconscious and involuntary processing of social information. For example, a study by Jellema et al (2009) found impairments in involuntarily interpreting social cues in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider this as one possible approach toward measuring implicit processes to make them comparable to explicit processes with the new Face Puzzle tasks. With regard to the literature on implicit processing of social information in general (e.g., Hudson et al, 2009; Hudson and Jellema, 2011) and related impairments in ASD (Jellema et al, 2009; Hudson et al, 2012; Senju, 2013), previous studies used mostly tasks that assessed unconscious and involuntary processing of social information. For example, a study by Jellema et al (2009) found impairments in involuntarily interpreting social cues in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the effect of an emotional expression on another psychological construct, e.g., racial attitudes, gender judgments, or attractiveness ratings (see, e.g., Devine et al, 2002; Amodio et al, 2004) are most often assessed indirectly via reaction times or eye movement patterns in response to the stimuli. Other indirect measures, for instance, investigate the influence of particular social cues (e.g., facial expressions or gaze direction) on judgments about body orientation or positioning (Hudson et al, 2009, 2012; Hudson and Jellema, 2011). However, when investigating subtle interindividual differences or impairments in a psychological construct, accuracy scores are of great value (Zaki and Ochsner, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that atypical predictive processing could explain altered perception and sensory experiences in ASD (e.g., Pellicano & Burr, 2012), but may also result in the associated social and communication deficits by affecting the individual's ability to predict others' actions and intentions (Sinha et al, 2014). In line with these theoretical propositions, several empirical studies have reported that individuals with ASD show differences in action prediction (Boria et al, 2009;Cattaneo et al, 2007;Hudson, Burnett, & Jellema, 2012;Schuwerk, Sodian, & Paulus, 2016;Senju et al, 2010;Vivanti, Trembath, & Dissanayake, 2014;Vivanti et al, 2011;Zalla, Labruyère, Clément, & Georgieff, 2010;Zalla, Labruyere, & Georgieff, 2006). Cattaneo and colleagues (2007), for instance, found that typically developing 5 to 9-year-old children show anticipatory muscle activation when performing and observing action sequences.…”
Section: Introductionmentioning
confidence: 94%
“…However, when participants with ASD did anticipate, their goal anticipations were similar to controls in this study. Interestingly, findings by Hudson, Burnett and Jellema (2012) suggest that while showing typical performance during action prediction, the strategy that individuals with ASD apply may differ from controls.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RM has been investigated within special populations 2 such as children born preterm and at term (Taylor & Jakobson, 2010), and those individuals with 3 autism spectrum disorder (Hudson, Burnett & Jellema, 2012). The typical RM effects observed 4 within past research have been hypothesised to reflect an anticipatory component of perception 5 which supports effective action (for a review of RM findings and theory see Hubbard, 2005).…”
mentioning
confidence: 99%